2022
DOI: 10.3389/fpubh.2022.870543
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Effectiveness Analysis of Screening Strategies Involving Non-Invasive Prenatal Testing for Trisomy 21

Abstract: IntroductionIn accordance with social development, the proportion of advanced maternal age (AMA) increased and the cost of non-invasive prenatal testing (NIPT) decreased.ObjectiveWe aimed to investigate the benefits and cost-effectiveness of NIPT as primary or contingent strategies limited to the high-risk population of trisomy 21 (T21).MethodsReferring to parameters from publications or on-site verification, a theoretical model involving 1,000,000 single pregnancies was established. We presented five screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…This finding was in line with a study conducted by Kostenko et al, which provided evidence supporting the cost-effectiveness of the universal NIPT for T13, T18, and T21 [44]. Similarly, the studies conducted by Walker et al in the US, Wang et al, Shang et al, and Xiao et al in China all provided evidence that the universal NIPT for T21 was a cost-effective approach [18,33,43,45]. In contrast, previous studies conducted by Evan et al from the US and Beulen et al from the Netherlands both revealed that the universal NIPT was currently not regarded as a cost-effective strategy for identifying T21 in newborns.…”
Section: Plos Onesupporting
confidence: 88%
See 1 more Smart Citation
“…This finding was in line with a study conducted by Kostenko et al, which provided evidence supporting the cost-effectiveness of the universal NIPT for T13, T18, and T21 [44]. Similarly, the studies conducted by Walker et al in the US, Wang et al, Shang et al, and Xiao et al in China all provided evidence that the universal NIPT for T21 was a cost-effective approach [18,33,43,45]. In contrast, previous studies conducted by Evan et al from the US and Beulen et al from the Netherlands both revealed that the universal NIPT was currently not regarded as a cost-effective strategy for identifying T21 in newborns.…”
Section: Plos Onesupporting
confidence: 88%
“…The trisomy risk assessment for these screening tests incorporates data from serum tests, NT results, and additional factors including age, weight, race, and gestation age of pregnant women [14]. According to previous studies, the detection rate for FTS have been observed to vary between 71.9% and 84% for T13, 71.9% and 97% for T18, and 71.4% and 91.7% for T21, with the false positive ranging from 0.5% to 7% [15][16][17][18][19]. For the quadruple test, the detection rate is around 80% for T18, ranging from 67% to 76.2% for T21, and the false positive varies between 5% to 14% [16,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%